THE EFFECT OF HEALTH EDUCATION TOWARD KNOWLEDGE OF THE ELDERLY IN MANAGEMENT RISK OF URINARY INCONTINENCE - Tina Yuli Fatmawati; Agustina Agustina (Jurnal Akademika Baiturrahim Jambi, 2018)
Indonesia as one of the countries in Asia is a country that experienced an increase in the elderly population rapidly. Survey in 11 Asian countries including Indonesia found 5,052 women suffering from urinary incontinence problems. Along with increasing age, the ability to hold urine is decreasing, so that the elderly have the potential to experience urinary incontinence so intervention is needed to deal with this problem. The purpose of this study was to determine the effect of health education on elderly knowledge in the management of the risk of urinary incontinence. This research is a quantitative research using the One Group pretest-posttest design. The research was conducted at the Posyandu Kasih in the capital city of Jambi. Sampling technique is accidental sampling, with a sample of 20 respondents, data analysis using univariate and bivariate with T dependen The result of this research that knowledge of the elderly before health education the highest value is 9, the lowest score was 4 with an average overall score of elderly is 6.30. After health education the highest value is 14 and the lowest was 10 with an average overall score of elderly is 12.05. there was an effect of health education on elderly knowledge in the risk management of urinary incontinence in Posyandu Kasih Ibu.